TEACHERS AS AGENTS OF CHANGE: SCHOOL-BASED DIAGNOSIS AND TREATMENT OF MALARIA POSITIVELY IMPACTS CHILD MORBIDITY - Ronald Mukisa; Andrew Macnab; Sharif Mutabazi; Rachel Steed (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Teachers in developing countries traditionally send home children found sick in class. Yet infection due to malaria is the principal reason a child will miss school in sub-Saharan Africa and the leading cause of death in school-aged children. Rapid diagnostic testing (RDT) and treatment with artemesinin combination therapy (ACT) is the management for malaria recommended by the World Health Organization (WHO) but RDT/ACT are not available in schools. Aims: To evaluate the impact on child morbidity from malaria of engaging teachers to provide RDT and administer ACT in primary schools in rural Uganda, using duration of absence from school as a surrogate measure of morbidity. Methods: This was a 2 year project.Pre-intervention (year 1) we trained teachers to identify probable infectious illness, conduct RDT, and administer ACT; conducted baseline evaluation of malaria knowledge, and monitored days of absence from school. Intervention (year 2) trained volunteer teachers administered RDT to children found to be sick at school and treated those positive with ADT; data collection was ongoing. Results: Teacher administered RDT/ACT was implemented and sustained in 4 rural schools (grades primary 1-5). Teachers participated willingly. Year 1 (pre-intervention) 953 of 1764 pupils were sent home due to illness; mean duration of absence from class was 6.5 (SD 3.17) school days. Year 2: (intervention with RDT/ACT) 1066 of 1774 pupils were identified as sick, 765/1066 (67.5%) tested positive by RDT for malaria and received ACT and their duration of absence fell to 0.59 (SD 0.64) school days (p<0.001); and overall absence decreased to 2.55 days from 6.5 in year 1 (p<0.001). Conclusion: RDT/ACT use by teachers as a school-based health practice is novel and reduced child morbidity significantly. Our model of engaging and training teachers represents a community empowerment approach applicable to other low-resource settings worldwide where malaria is endemic and morbidity high.